Apexification in a non-vital tooth: By control of infection - Basgauda R Patil; Priti B Patil; Amol N Patil (Wolters Kluwer Medknow Publications, 2010)
Endodontic management of immature non-vital permanent teeth in young pediatric patients is a great challenge to dentists. When the pulp of an incompletely formed tooth loses its vitality, then the entire root system has also lost its ability to continue to develop. The walls of the root canals are frequently divergent and open apices make debridement and obturation difficult. Thus, closure of the root apex is very essential for the success of endodontic treatment. Many different materials are used for the apexification procedure, for apical barrier formation and healing. However, in this present case the apical closure was achieved only by means of infection control.